Defense Science Board Summer Study on Autonomy - David, Ruth A; Nielsen, Paul; Llorens, Ashley J. (2016)
At the request of the Under Secretary of Defense for Acquisition, Technology, and Logistics (USD(AT and L)), the Defense Science Board (DSB) conducted a study on the applicability of autonomy to Department of Defense (DoD) missions. The study concluded that there are both substantial operational benefits and potential perils associated with the use of autonomy. Autonomy delivers significant military value, including opportunities to reduce the number of warfighters in harms way, increase the quality and speed of decisions in time-critical operations, and enable new missions that would otherwise be impossible. Autonomy is by no means new to the DoD. Fielded capabilities demonstrate ongoing progress in embedding autonomous functionality into systems, and many development programs already underway include an increasingly sophisticated use of autonomy. Autonomy also delivers significant value across a diverse array of global markets. Both enabling technologies and commercial applications are advancing rapidly in response to market opportunities. Autonomy is becoming a ubiquitous enabling capability for products spanning a spectrum from expert advisory systems to autonomous vehicles. Commercial market forces are accelerating progress, providing opportunities for DoD to leverage the investments of others, while also providing substantial capabilities to potential adversaries. This study concluded that DoD must accelerate its exploitation of autonomy both to realize the potential military value and to remain ahead of adversaries who also will exploit its operational benefits.
Published by the Office of the Under Secretary of Defense for Acquisition, Technology and Logistics